A trade-off design of microstrip broadband power amplifier for UHF applications - Mohamed Ribate; Rachid Mandry; Jamal Zbitou; Larbi El Abdellaoui; Ahmed Errkik; Mohamed Latrach; Ahmed Lakhssassi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper, the design of a Broadband Power Amplifier for UHF applications is presented. The proposed BPA is based on ATF13876 Agilent active device. The biasing and matching networks both are implemented by using microstrip transmission lines. The input and output matching circuits are designed by combining two broadband matching techniques: a binomial multi-section quarter wave impedance transformer and an approximate transformation of previously designed lumped elements. The proposed BPA shows excellent performances in terms of impedance matching, power gain and unconditionally stability over the operating bandwidth ranging from 1.2 GHz to 3.3 GHz. At 2.2 GHz, the large signal simulation shows a saturated output power of 18.875 dBm with an output 1-dB compression point of 6.5 dBm of input level and a maximum PAE of 36.26%.